Participative Urban Health and Healthy Aging in the Age of AI 19th International Conference, ICOST 2022, Paris, France, June 27-30, 2022, Proceedings - Aloulou, Hamdi; Abdulrazak, Bessam; de Marassé-Enouf, Antoine; Mokhtari, Mounir (Lecture Notes in Computer Science, 2022)
This open access book constitutes the refereed proceedings of the 18th International Conference on String Processing and Information Retrieval, ICOST 2022, held in Paris, France, in June 2022. The 15 full papers and 10 short papers presented in this volume were carefully reviewed and selected from 33 submissions. They cover topics such as design, development, deployment, and evaluation of AI for health, smart urban environments, assistive technologies, chronic disease management, and coaching and health telematics systems.